Trends and rainfall tropicalization in Parana State, south of Brazil - Nascimento Jr, Lindberg; Rodrigues Silvestre, Miriam [UNESP]; Santa'Anna Neto, Joao Lima [UNESP] (Centro Ciencias Atmosfera Unam, 2020)
In order to detect areas and periods of rainfall reduction and increase in Parana State, south of Brazil, the objective of this manuscript is to analyze, spatially and temporally, rainfall trends from 1976 to 2011. Monthly data were collected on accumulated rainfall (mm) from 63 pluviometric stations distributed throughout the study area. The data were grouped into quarterly (autumn, winter, spring, and summer), seasonal (dry and rainy season), and annual values. All values were evaluated for homogeneity and trends using the Mann-Whitney-Pettitt, Mann-Kendall, and linear regression tests. The results indicate a rainfall transition detected in the period 1991 to 1999, with a maximum change point in 1993. The trends indicate an average increase of 4.03 mm in the rainy season, mainly in the sectors that are predominately subtropical and coastal climates. These results corroborate in a better explanation rainfall patterns and variability in the tropical regions and the Southern Hemisphere, and imply a moderate process of rainfall tropicalization in the subtropical climate of Parana State.
Keywords: precipitation; variability; trends; tropicalization; Parana State; Brazil